CERITA BERGAMBAR UNTUK MENGUATKAN PENDIDIKAN KARAKTER ANAK USIA DINI DI TK BAHAGIA SURABAYA - Istiana, Istiana; Yusron Maulana El-Yunusi, Muhammad (Universitas Muhammadiyah Surabaya, 2024)
Character education is a very important education and must continue to be strengthened in an institution and society. Through the media of picture story books, character education can be strengthened effectively. The aim of this research is to find out the extent of the effectiveness of picture story books in stimulating the development of early childhood in the Bahagia Surabaya Kindergarten institution, the research method used is the Applied Qualitative method where to stimulate children's development it is done by reading picture story books not only at school but also by parents at home. This research was carried out by interviewing teachers and parents. From several observations it can be found that from several children observed there are indications that some children's development is starting to be stimulated well, thus it can be concluded that picture story books are very effective in stimulating children's development by reading them regularly and continuously both in institutions and continuing in home, however, children also need to continue to be guided and directed to continue to behave according to the desired character.